PENGARUH BUDAYA KERJA, KOMPETENSI DAN KOMPENSASI TERHADAP KINERJA PEGAWAI DI LINGKUNGAN RUMAH SAKIT UMUM DAERAH (RSUD) LUBUK SIKAPING KABUPATEN PASAMAN PROVINSI SUMATERA BARAT - Ardi, A; Djati, S. Pantja (SWOT : Jurnal Ilmiah Ilmu Manajemen, 2019)
The performance of employees, especially in the health sector in Indonesia in general is still a problem that requires immediate solutions for improvement. many society complain about not yet maximally Hospital services. The aim of this study is to determine the influence of work culture, competence, and compensation on the performance of employees in the environment of Regional General Hospital (RSUD) Lubuk Sikaping, either partially or simultaneously. This type of research uses a quantitative approach with the survey method that uses primary data obtained from the questionnaires. The population in this research is all employees in the environment of Regional Public Hospital (RSUD) Lubuk Sikaping which has 250 employees and sampling technique using Simple random sampling which found 72 employees as sample. Those data were analyzed by using simple linear regression analysis and multiple T test, F test, coefficient of determination test, and accompanied by classical assumption test. The results showed that simultaneously the variables of work culture, competence, and compensation have a positive and significant influence on employee performance. The results showed that Partial test the work culture and competence have a positive and significant effect on employee performance, whereas compensation has positive, but not significant effect on employee performance